2017
DOI: 10.1007/s13205-016-0578-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of genetic diversity in Sesamum indicum L. using RAPD and SSR markers

Abstract: Sesame (Sesamum indicum L.) is an ancient oilseed crop known for its nutty seeds and high-quality edible oil. It is an unexplored crop with a great economic potential. The present study deals with assessment of genetic diversity in the crop. Twenty two RAPD and 18 SSR primers were used for analysis of the 47 different sesame accessions grown in different agroclimatic zones of India. A total of 256 bands were obtained with RAPD primers, of which 191 were polymorphic. SSR primers gave 64 DNA bands, of which all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
(76 reference statements)
2
11
3
Order By: Relevance
“…In contrast, a very high level of genetic diversity among sesame accessions by means of RAPD molecular markers has been reported by Bhat et al (1999), Ercan et al (2004), Akbar et al (2011), Dar et al (2017) and Quenum and Yan (2017). The present study detected a high level of polymorphism for sesame between the different geographical areas of West Bengal.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In contrast, a very high level of genetic diversity among sesame accessions by means of RAPD molecular markers has been reported by Bhat et al (1999), Ercan et al (2004), Akbar et al (2011), Dar et al (2017) and Quenum and Yan (2017). The present study detected a high level of polymorphism for sesame between the different geographical areas of West Bengal.…”
Section: Discussioncontrasting
confidence: 75%
“…RAPD markers were utilized in this study to evaluate the level of genetic variation among the 15 germplasms of S. indicum L. collected from different districts of West Bengal, India. The RAPD technique has been chosen as it does not require any previous knowledge on DNA sequence of this species, is an inexpensive and easy to use for evaluating the degree of genetic diversity in sesame and many other plant species (Akbar et al 2011;Bhat et al 1999;Ercan et al 2004;Salazar et al 2006;Sangwan et al 2001;Sharma et al 2009;Vieira et al 2003;Singh et al 2017;Dar et al 2017). Ten RAPD primers detected sufficient genetic variation within fifteen sesame germplasms to allow for complete Correlation Acc-1 Acc-2 Acc-3 Acc-4 Acc-5 Acc-6 Acc-7 Acc-8 Acc-9 Acc-10 Acc-11 Acc-12 Acc-13 Acc-14 Acc-15 Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphic information content (PIC) ranged from 0.36 (CU-ESSR-18) to 0.82 (CU-ESSR-26 (Table 1) with a low average of 0.607, which can be partly explained by the fact that all microsatellites were developed from ESTs, which are generally less variable than unexpressed regions of the genome. This value of PIC is slightly lower than 0.72 which was reported by Yepuri et al (2013) but higher than reported by Anandan et al 2017and Dar et al (2017). Based on PIC values, CU-ESSR-26 (0.82) appeared to be the most informative marker.…”
Section: Resultsmentioning
confidence: 46%
“…All six primers were suitable for use as markers in detecting genetic variations in mangroves because they can produce polymorphic bands. Polymorphic data in RAPD is the result of several events: (i) the insertion of large DNA fragments between the primer attachment sites that exceed the ability of PCR so that no fragments are detected, (ii) small insertions or deletions of DNA strands that cause changes in the size of amplification fragments, (iii) deletion of one of the primer attachment sites resulting in loss of fragments or increased fragment size, and (iv) substitution of one nucleotide in one or two primer target sites that affect the annealing process, which results in the presence or absence of polymorphisms or changes in fragment size (Dar et al 2017).…”
Section: Strength Of Rapd Primermentioning
confidence: 99%